2009
DOI: 10.2522/ptj.20080241
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprosthesis Peroneal Functional Electrical Stimulation in the Acute Inpatient Rehabilitation Setting: A Case Series

Abstract: It is possible that peroneal FES delivered through a neuroprosthesis during acute stroke recovery may improve gait outcomes. Research is needed to determine proper duration and timing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…In stroke, FES is generally used to improve ankle dorsiflexion during the swing phase of the gait cycle to correct a foot drop and to decrease the energy expenditure during walking [6,14,15]. FES also has benefits in improving gait through repetitive practice during retraining by restoring the motor programing of a more normal gait performance in stroke populations [9,15].…”
Section: Discussionmentioning
confidence: 98%
“…In stroke, FES is generally used to improve ankle dorsiflexion during the swing phase of the gait cycle to correct a foot drop and to decrease the energy expenditure during walking [6,14,15]. FES also has benefits in improving gait through repetitive practice during retraining by restoring the motor programing of a more normal gait performance in stroke populations [9,15].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, a range of training programs for gait, such as training using functional electrical stimulation 7) , treadmill training 8) , task orientated training 9) , and augmented reality training 10) have been designed.…”
Section: Introductionmentioning
confidence: 99%
“…29 Studies have suggested that peroneal nerve FES during walking improves gait and PCI in patients with chronic stage 22,26 and during the acute stage of recovery. 30 In a recent randomized trial with 28 chronic hemiplegics reported that the FES stimulation to dorsiflexors and plantarflexors combined with daily walking, improved the walking ability, muscle strength, and spasticity of adults with hemiplegia. 31 However, there has been no study on the combined effect of FES with the conventional therapy in subacute and chronic stages of stroke patients.…”
Section: Introductionmentioning
confidence: 98%